The Influence of Venture Capital on the Pre-IPO Technological Innovation of Chinese Companies - Qi, Anji (2020)
This paper investigates the influence of venture capital on pre-IPO technological innovation in Chinese firms, combining theoretical and empirical analyses for analysis. In terms of indicators to measure the innovation capability of companies, this paper selects the proportion of R&D expenses to main business revenue and the proportion of R&D employees to total employees as indicators to measure innovation input, and selects the number of patents and software copyrights owned by enterprises before IPO as indicators to measure innovation output.